PENGEMBANGAN ASIPP (ALAT ASESMEN IBU POSTPARTUM) MENGGUNAKAN PEMODELAN RASCH - Ardiyanti, Difa; Dinni, Siti Muthia (Jurnal Psikologi, 2019)
Postpartum Depression (PPD) is a mental health problem in mothers that has a serious impact on mothers, children and families. Late detection and treatment can endanger the lives of mothers and their babies. Unfortunately, in Indonesia, research on developing an early detection instruments of PPD based on potential factors or the risk of PPD has not been widely implemented. This study aims to develop a more comprehensive assessment tool for postpartum mothers based on psychological variables that are theoretically correlated with PPD (emotional regulation, maternal confidence, and marital satisfaction) using Rasch model to obtain information regarding psychometric properties of Alat Asesmen Ibu Postpartum (ASIPP). The subjects of this study were 90 women with characteristics that had just given birth between the last 2-24 weeks. Based on the analysis using the Winsteps program, the results of the reliability coefficient of the maternal self-confidence scale and emotion regulation scale were the same which was 0,82 and the reliability coefficient of the marriage satisfaction scale was 0,91. All of the scales were able to reveal psychological constructs according to the objectives of measurement (unidimensional). The maternal self-confidence scale consists of 15 items that fit model. The emotion regulation scale consists of 12 items that fit model and the marriage satisfaction scale consists of 27 items that fit model. Overall, it can be concluded that Alat Asesmen Ibu Postpartum (ASIPP) which contains a maternal self-confidence scale, emotion regulation scale, and marriage satisfaction scale has good psychometric properties so that it can be used to measure maternal self-confidence, emotion regulation, and marriage satisfaction of postpartum women.